Code Switching and Code Mixing Study in “Hitam Putih” Talk Show Program - Ayu Wulandari (Vivid: Journal of Language and Literature, 2021)
This research aimed to investigate the kinds of code-switching and code-mixing used by the participants in Hitam Putih talk show. By analysing each statement of code-switching and code mixing which is spoken by the speakers of Hitam Putih talk show, the researcher tried to analyse the point of view of Sociolinguistics to see the phenomena of the code-switching and code-mixing used by the participants in the talk show. The approach of this study is qualitative. The researcher obtained the data from the program channel on the YouTube by taking notes. The finding of this study shows that the host of the talk show used code switching and code mixing in order to make the audiences understand the conversation between the presenter and the guest. Besides, the guest whose first language is not Indonesian in fact she tried to speak Indonesian in order to appreciate the Indonesian audiences. Another purpose of doing the code switching and code mixing on that program is to educate the audiences to know more about what the guest said in English.